POLA PRAKTISI BIMBINGAN DAN KONSELING TERHADAP SISWA HOMESCHOOLING DALAM MENGEMBANGKAN POTENSI DIRI - Santoso, Hajar Ahmad; Maulidiyah, Rizqi (Jurusan Bimbingan dan Konseling, 2018)
Homeschooling practices still generate a variety of contrasting responses to their relevance and effectiveness. This study aims to map the relationship patterns of homeschooling students with the development of self potential that has been through the analysis phase. The analysis conducted focuses on mapping relationships: a) research arrangements; b) target sample; c) methods and instruments used; d) general focus or issues discussed; and e) patterns in findings from student development. It was found that this study focused more on evaluating the effectiveness and relevance of homeschooling as an alternative to traditional schools, especially in the field of effective learning experiences and developments in the social media world. Apart from the advantages of homeschooling practice, this article also finds harmony from the importance of guidance and counseling conducted by the teacher in improving students' self-potential. So that this research provides recommendations for further effective homeschooling practices